Regional inflation dynamics within and across euro area countries and a comparison with the US - Günter W. Beck; Kirstin Hubrich; Massimiliano Marcellino (European Central Bank (ECB), 2006)
We investigate co-movements and heterogeneity in inflation dynamics of different regions within and across euro area countries using a novel disaggregate dataset to improve the understanding of inflation differentials in the European Monetary Union. We employ a model where regional inflation dynamics are explained by common euro area and country specific factors as well as an idiosyncratic regional component. Our findings indicate a substantial common area wide component, that can be related to the common monetary policy in the euro area and to external developments, in particular exchange rate movements and changes in oil prices. The effects of the area wide factors differ across regions, however. We relate these differences to structural economic characteristics of the various regions. We also find a substantial national component. Our findings do not differ substantially before and after the formal introduction of the euro in 1999, suggesting that convergence has largely taken place before the mid 90s. Analysing US regional inflation developments yields similar results regarding the relevance of common US factors. Finally, we find that disaggregate regional inflation information, as summarised by the area wide factors, is important in explaining aggregate euro area and US inflation rates, even after conditioning on macroeconomic variables. Therefore, monitoring regional inflation rates within euro area countries can enhance the monetary policy maker's understanding of aggregate area wide inflation dynamics.
Keywords: E31; E52; E58; C33; 330; common factor models; euro area and US; regional inflation dynamics; Inflation; Räumliche Verteilung; Raumstruktur; Vergleich; EU-Staaten; USA